On a Mixed Nonlinear One Point Boundary Value Problem for an Integrodifferential Equation. (18th March 2008) - Mesloub, Said
Abstract : This paper is devoted to the study of a mixed problem for a nonlinear parabolic integro-differential equation which mainly arise from a one dimensional quasistatic contact problem. We prove the existence and uniqueness of solutions in a weighted Sobolev space. Proofs are based on some a priori estimates and on the Schauder fixed point theorem. we also give a result which helps to establish the regularity of a solution.